Sport-related physical activity in tourism: an analysis of antecedents of sport based applications use - Pérez-Aranda, Javier Ramón; González-Robles, Eva María; Alarcón-Urbistondo, María del Pilar (Springer Link, 2021)
Wearable devices and mobile applications (hereafter referred to as apps) used in sport and physical activity have widely changed the way sport is practised. However, experts still understand little about the antecedents of tourists’ sport apps use. Draw- ing on the theory of reasoned action, this study examined attitudinal and norm-based factors that influence users’ continuance intention towards sport apps as predictors of use in trips. A questionnaire was designed based on the existing literature in order to collect the relevant data from centres and places for doing sport. The final sample consisted of 362 sport practitioners and users of sport apps, whose responses were used to test the model. The results indicate that all attitudinal factors (i.e. perfor- mance expectancy, effort expectancy, perceived satisfaction, perceived enjoyment and perceived gamification) and norm-based factors (i.e. social influences) affect users’ continuance intention towards Smart Internet of Things sport apps. In addi- tion, the respondents’ continuance intention towards these apps affects their sport apps use in trips. Theoretical and managerial implications for the tourism industry are discussed.
Keywords: Turismo - Proceso de datos; Deportistas - Proceso de datos; Informática - Aplicaciones; Use in trips; Theory of reasoned action; Sport app; Partial least squares